2011
DOI: 10.1103/physrevb.84.165437
|View full text |Cite
|
Sign up to set email alerts
|

Interference effects in phtalocyanine controlled by H-H tautomerization: Potential two-terminal unimolecular electronic switch

Abstract: We investigate the electrical transport properties of two hydrogen tautomer configurations of phthalocyanine (H 2 Pc) connected to cumulene and gold leads. Hydrogen tautomerization affects the electronic state of H 2 Pc by switching the character of molecular orbitals with the same symmetry close to the Fermi level. The near degeneracy between the HOMO and HOMO-1 leads to pronounced interference effects, causing a large change in current for the two tautomer configurations, especially in the low-bias regime. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
(104 reference statements)
2
22
1
Order By: Relevance
“…NDR has been found in a variety of molecular devices, such as phenylethynylene oligomer (OPE) molecular junctions, [ 5 , 6 ] a single benzene ring with a nitro side group [ 23 ] or by an external gate fi eld, [ 24 ] mirror-symmetrical straight carbon nanotube heterojunctions, [ 25 ] carbon nanowires contacted directly to two asymmetric electrodes, [ 26 ] a squashed C 60 molecular device, [ 27 ] and a squeezed carbon monatomic ring, [ 28 ] etc. More recently, Prasongkit et al [ 29 ] studied interference effects in phthalocyanine controlled by H-H tautomerization and found that gold-H 2 Pc-gold junctions show pronounced NDR at high bias voltage, as well as weak NDR at intermediate bias. However, signifi cant NDR has not yet been observed in a single donor-acceptor molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDR has been found in a variety of molecular devices, such as phenylethynylene oligomer (OPE) molecular junctions, [ 5 , 6 ] a single benzene ring with a nitro side group [ 23 ] or by an external gate fi eld, [ 24 ] mirror-symmetrical straight carbon nanotube heterojunctions, [ 25 ] carbon nanowires contacted directly to two asymmetric electrodes, [ 26 ] a squashed C 60 molecular device, [ 27 ] and a squeezed carbon monatomic ring, [ 28 ] etc. More recently, Prasongkit et al [ 29 ] studied interference effects in phthalocyanine controlled by H-H tautomerization and found that gold-H 2 Pc-gold junctions show pronounced NDR at high bias voltage, as well as weak NDR at intermediate bias. However, signifi cant NDR has not yet been observed in a single donor-acceptor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] All results hitherto showed that carbon chains have exceptional electronics characteristics. [29][30][31][32][33][34][35][36][37][38][39][40] For example, Lang and Avouris [ 37 , 38 ] reported that when carbon chains were connected directly to two Au electrodes, the zero-bias conductance would oscillate as a function of the number of carbon atoms in the chains. Recently, Prasongkit et al [ 40 ] showed that the transmission spectrum and the conductance for carbon chains with a cumulene confi guration depend only weakly on applied bias and the I -V characteristic is nearly linear over a bias region of ± 1 V.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum interference is the key feature of coherent quantum transport, and DQI plays an essential role in the H-H tautomerization molecular switch [17] as well as the quantum interference effect transistor (QuIET) [18]. Recently, DQI has been experimentally observed in electron transport through a cross-conjugated molecular junction at room temperature [12].…”
mentioning
confidence: 99%
“…The monotonously high conductance of the ON state can be understood from Figure 3, where it can be seen that more of the high-transmission region is included within the bias window as the bias voltage is increased. In the OFF state at V bias = 0 V, the transmission function shows a transmission dip, or antiresonance, due to destructive zero-bias conductance ratio [the ratio between T(E) in the ON and OFF states] of ∼10 4 , which is much higher than the value of 431 reported in ref 12). The the ON state also has a transmission dip at −0.461 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…12 However, NEGF-DFT calculations with GGA as well as the local density approximation (LDA) have been widely employed. 14,15 More importantly, the QIE that occurs between the HOMO and LUMO derives from the characteristics and symmetry of the molecular orbitals rather than from their precise energetic positions.…”
Section: ■ Model and Computational Detailsmentioning
confidence: 99%